Delayed pain relief in patients with trigeminal neuralgia following microvascular decompression: A single-central retrospective study - Zhang, Zhengyu; Wang, Fang; Yu, Feng; Kwok, Sze Chai; Yin, Jia (Frontiers in Neurology, 2022)
Background: Compared to hemifacial spasm after microvascular decompression (MVD), delayed relief (DR) rarely occurs in patients with trigeminal neuralgia (TGN). Objective: To analyze the characteristics of post-MVD DR in TGN patients to provide useful clues for the clinical differential diagnosis of postoperative DR. Methods: The clinical data of all patients with TGN who underwent MVD in our center from January 1, 2016, to December 31, 2020, were reviewed retrospectively. Results: In 272 TGN MVD patients, DR occurred in 9 patients (3.3%) during the follow-up periods of 1-6 years. During surgery, all 9 DR-TGN patients were identified as having neurovascular conflicts (NVCs), involving the offending artery (OA) in 8 patients (2 OAs in 2 patients) and both an artery and a vein in the other patient. The compression site was near the root entry zone (REZ) in most DR patients (7/9). DR was relieved in 7 patients within 5 days after surgery and within 30 days in the other 2 patients. No recurrence or serious complications were observed within the mean 4 (1-6)-year follow-up duration. Conclusion: DR rarely occurs in TGN patients after MVD. NVCs located at the REZ and NVC of grade III may be two important factors contributing to DR in TGN patients. DR may occur when the pain gradually improves after the operation and responds effectively to a small dose of carbamazepine. The recurrence rate of TGN seems even lower in such patients.